Evaluation of forage production performance and prediction of introduction adaptability for different Avena sativa germplasms in the southeast edge of the Qinghai-Tibet plateau - Zhao, Ting; Lu, Huanhuan; Zhang, Fan; Zheng, Yuying; Tang, Liuban; Zhang, Changbing; Ma, Yongcai; Cai, Rongjia; Xie, Wengang (Frontiers in Plant Science, 2025)
IntroductionThe grassland degradation and harsh climate in the Qinghai-Tibet Plateau (QTP) have constrained forage production, thereby impeding the development of animal husbandry in pastoral areas of China. The effective cultivation of high-yielding Avena sativa could help alleviate this constraint.MethodsThis study comprehensively evaluated the forage yield and related agronomic traits of 62 A. sativa germplasms. Additionally, the introducing adaptability of different germplasms was predicted across various regions of the QTP.ResultsThe results indicated that: (1) 43 of 62 germplasms could successfully completed the fertility period in the eastern edge of the QTP; (2) Fresh and hay grass yield were significantly positively correlated with absolute plant height, flag leaf length, flag leaf width, flag leaf area, flag-second leaf length, flag-second leaf width, flag-second leaf area, number of total tiller, number of vegetative tiller, stem to leaf ratio of hay, thick of second stem internode, spike length, and root depth, while significantly negatively correlated with thousand kernel weight; (3) Fresh and hay grass yield were directly affected by flag-second leaf length, flag-second leaf width, flag-second leaf area, number of total tiller, number of fertile tiller, and stem to leaf ratio of hay; (4) A. sativa germplasm AS55 exhibited the highest comprehensive forage performance under field conditions, followed by AS39, AS48, AS28, AS41, and AS20; (5) The potential spatial distribution of A. sativa was concentrated in the southeastern QTP, with its distribution being significantly affected by hydrothermal conditions. Moreover, the potential distribution pattern of high suitability regions showed an expanding trend over time; (6) 15 A. sativa germplasms had varying degrees of introduction adaptability in 23 municipal-level administrative regions within the QTP. The potential suitable area for introducing different germplasms was 7.81×105 km2 in the current period and 2.68×105 km2 in the future period. the area of regions with high introduction adaptability increased from 1.60×103 km2 in the current period to 1.38×104 km3 in the future period.DiscussionIn this study, evaluations of forage production performance and predictions of introduction adaptability were conducted for 62 A. sativa germplasms at the eastern edge of the QTP. The findings aim to provide a theoretical basis for the collection, preservation, and utilization of A. sativa germplasm resources, as well as valuable insights for the cultivation and protection of plants in the QTP.